English Education Students' Perception of the Use of ChatGPT in Writing Articles - Hasanah, Uswatun; Nurcholis, Ivan Achmad (Pubmedia Jurnal Pendidikan Bahasa Inggris, 2024)
ChatGPT is an artificial intelligence-based machine technology developed by the OpenAI company. ChatGPT is trained to be able to simulate human conversations such as answering questions and interacting on various topics. This research uses a qualitative approach with a descriptive research type. Data collection techniques can be obtained through questionnaires. The purpose of this study is to find out the perceptions of students towards the use of ChatGPT in writing articles. The target of the research is 7th semester students who have published articles. The results showed that the percentage of positive students towards the use of ChatGPT and there are also some students who are not in agreement with the use of GhatGPT in writing articles.